Implementasi Metode HOT FIT pada Evaluasi Tingkat Kesuksesan Sistem Pengisian KRS Terkomputerisasi - Marisha Ayuardini; Anggraeni Ridwan (Faktor Exacta, 2019)
This study aims to: (1) determine the success rate of computerized study plan card filling systems at the University Gunadarma using the HOT Fit method based on the results of evaluations from users and; (2) knowing the effects of measurement characteristics of the implementation of the HOT Fit method in evaluating the success rate of computerized study plan card filling systems at Gunadarma University. The method used for assessing this system uses the HOT Fit method which consists of 7 characteristics, namely System Quality (Ks), Information Quality (Ki), Service Quality (Kl), System Users (Ps), User Satisfaction (Kp), Benefits (Mn) and Organizational Structure (So) by using purposive sampling technique. The discussion chapter is deepened by triangulation, namely interviews, documentation and observation. The distribution of the questionnaire was carried out to users, namely Information Systems students in the 2018-2019 academic year as many as 96 samples. The analysis is done through a test case of each HOT Fit character. The results of this study indicate that: (1) computerized KRS filling system as a whole has a good interpretation according to the HOT Fit method with a value of 2.91; (2) the quality of the final result of the Ks character with an interpretation value of 2.98 (good), Ki with a value of 2.89 (good), Kl with a value of 2.9 (good), Ps with a value of 2.92 (good), Ks with a value of 2.64 (good), Mn with a value of 2.74 (good) and So with a value of 3.27 (very good) based on the HOT Fit method.Keywords: HOT fit, success rate of system, evaluation, characteristic measurement